2018
DOI: 10.7717/peerj.5415
|View full text |Cite
|
Sign up to set email alerts
|

Repercussion of nonsteroidal anti-inflammatory drugs on the gene expression of human osteoblasts

Abstract: BackgroundNonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used in clinical practice, which can have adverse effects on the osteoblast. The objective of this study was to determine the effect of NSAIDs on the osteoblast by analyzing the gene expression of different markers related to osteoblast maturation and function when treated in vitro with different NSAIDs.MethodsThree human osteoblast lines from bone samples of three healthy volunteers were treated with 10 µM acetaminophen, indomethacin, keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Paracetamol was also investigated in this study; it is not a typical NSAID, but it appears to inhibit COX-2 to a degree similar to that of selective COX2 inhibitors and other NSAIDs (40). However, the underlying mechanism is believed to be more complex with several factors involved, including inhibition of PG synthesis, induction of apoptosis by different pathways and cell cycle arrest (41,42). In this study, we did not observe any significant reduction in the proliferation capacity (except for 10 -5 M and 15-day treatment) or osteogenic maturation of the paracetamol-treated MC3T3-E1 cells at 10 -6 M. A previous study has reported inhibition of ALP activity of MC3T3-E1 but a higher doses of paracetamol (33-330 µM) (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracetamol was also investigated in this study; it is not a typical NSAID, but it appears to inhibit COX-2 to a degree similar to that of selective COX2 inhibitors and other NSAIDs (40). However, the underlying mechanism is believed to be more complex with several factors involved, including inhibition of PG synthesis, induction of apoptosis by different pathways and cell cycle arrest (41,42). In this study, we did not observe any significant reduction in the proliferation capacity (except for 10 -5 M and 15-day treatment) or osteogenic maturation of the paracetamol-treated MC3T3-E1 cells at 10 -6 M. A previous study has reported inhibition of ALP activity of MC3T3-E1 but a higher doses of paracetamol (33-330 µM) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies concerning changes in the osteogenic marker gene expression as well as the antigenic profile of the pre-osteoblastic cells will provide more insight into the mechanism of the action of NSAIDs on these cells. Some gene expression studies have already been conducted on human osteoblasts and the osteosarcoma osteoblast-like cell line MG63 (42). Regarding MC3T3-E1, Nagano et al found that celecoxib inhibited the mRNA expression of both Runx2 and Alp (47).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were labeled by direct staining with the monoclonal antibodies (MAbs) CD54, CD80, CD86, and HLA-DR (ICAM-1 monoclonal antibody [MEM-111], FITC; human CD80 [B7-1, BB1], FICT; human CD86 [B7-2, B70], FICT; and anti-human HLA-DR [Clas II], FICT; respectively, from Invitrogen, Thermo Fisher Scientific, Spain). Cells were subsequently analyzed by flow cytometry (FASC Canton II, SE Becton Dickinson, Palo Alto, CA) as previously described Melguizo-Rodriguez et al 8.…”
Section: Methodsmentioning
confidence: 99%
“…Our study showed that ketoprofen was the one that reduced the levels of alkaline phosphatase the most at 15 and 30 days compared to diclofenac (p= 0.015 and p= 0.001, respectively). Similarly, Melguizo-Rodríguez et al [17] carried out a study to determine the effect of paracetamol, indomethacin, ketoprofen, diclofenac, ibuprofen, ketorolac, naproxen and piroxicam on three lines of human osteoblasts from bone samples, finding that ketoprofen and diclofenac decreased RUNX-2 and alkaline phosphatase expression compared to control. Even though the study by Melguizo-Rodríguez et al [17] was in vitro compared to our study, the cellular behavior is similar from the metabolic and biochemical point of view.…”
Section: Osteoblast Count At 15 and 30 Daysmentioning
confidence: 99%
“…Similarly, Melguizo-Rodríguez et al [17] carried out a study to determine the effect of paracetamol, indomethacin, ketoprofen, diclofenac, ibuprofen, ketorolac, naproxen and piroxicam on three lines of human osteoblasts from bone samples, finding that ketoprofen and diclofenac decreased RUNX-2 and alkaline phosphatase expression compared to control. Even though the study by Melguizo-Rodríguez et al [17] was in vitro compared to our study, the cellular behavior is similar from the metabolic and biochemical point of view. On the other hand, Manzano-Moreno et al [18] carried out a study that evaluated the effects of NSAIDs on the expression of vascular endothelial growth factor (VEGF) in two osteoblast cell lines, finding that paracetamol, indomethacin, ketoprofen, diclofenac, ibuprofen, ketorolac, naproxen or piroxicam significantly reduced VEGF expression independently of the cell line (primary culture osteoblasts and human osteosarcoma cell line MG63); Furthermore, they mentioned that more studies are needed to elucidate the signaling mechanism by which NSAIDs appear to have undesired effects on osteoblasts.…”
Section: Osteoblast Count At 15 and 30 Daysmentioning
confidence: 99%